Kewirausahaan Perempuan (Produksi Abon Ayam) dalam Upaya Pemberdayaan Perempuan di Desa Keresek Kecamatan Cibatu Kabupaten Garut - Lilis Irmawatie dan Akhmad Khori (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2013)
Women Empowerment through training in shredded-chicken (Bahasa: Abon Ayam) business at Keresek Village, Cibatu, Garut, is an essential to be carried out in terms of creating efforts to help them improve the family’s welfare. The potential of natural and human resources supported the empowerment, especially the existence of shredded-chicken named Aisyah Home Industry which was willing to be a partner in this activity. Entrepreneurial women via training skills in the shredded-chicken manufacture considering women empowerment aims to enhance their skills so that they are able to earn income for supporting the family's welfare as well as efforts to help developing home industry business partners in shredded-chicken in order to compete markets around. The activities implementation carried out by training, mentoring and ongoing post-training. Women empowerment through entrepreneurship training of shredded-chicken production, has been able to provide additional income that can support the family economy. After being held continuous mentoring, shredded-chicken home industry as partner can produce on a regular basis and marketing began to spread outside the village, the quality production quality is maintained and packaging models are competitive